1990
DOI: 10.1007/bf00404097
|View full text |Cite
|
Sign up to set email alerts
|

A trial of nicotinamide in newly diagnosed patients with Type 1 (insulin-dependent) diabetes mellitus

Abstract: Various agents have been tried in subjects with newly diagnosed Type 1 (insulin-dependent) diabetes mellitus in an attempt to preserve Beta-cell function. In this double-blind study, nicotinamide or placebo were given for one year to 35 children and adolescents with newly-diagnosed Type 1 diabetes. All subjects were within six weeks of diagnosis and were between the ages of 6 and 18 years. Nicotinamide, a poly-(ADP-ribose) synthetase inhibitor, was given in a dose of 100 mg/year of age up to a maximum of 1.5 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
3

Year Published

1994
1994
2010
2010

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 17 publications
0
28
0
3
Order By: Relevance
“…Older clinical studies using nicotinic acid or impure preparations of nicotinamide reported relatively frequent liver enzyme abnormalities [6, 33±35] although more recent studies using a purified form of nicotinamide have not detected any noteworthy adverse effects on liver enzymes [13,15,17,20,36]. This experience is described in more detail below.…”
Section: Liver Toxicitymentioning
confidence: 95%
“…Older clinical studies using nicotinic acid or impure preparations of nicotinamide reported relatively frequent liver enzyme abnormalities [6, 33±35] although more recent studies using a purified form of nicotinamide have not detected any noteworthy adverse effects on liver enzymes [13,15,17,20,36]. This experience is described in more detail below.…”
Section: Liver Toxicitymentioning
confidence: 95%
“…Residual insulin secretion facilitates metabolic control and decreases the risk of keto-acidosis [3], and even modest beta cell function, with stimulated C-peptide above 0.2 nmol/l, may reduce long-term complications [4]. Type 1 diabetes is an autoimmune disease [5]; however, most attempts to use immune intervention to preserve residual beta cell function have achieved limited benefits or have been associated with adverse effects [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Treatment with anti-CD3 monoclonal antibodies appears to be the most promising treatment to date, but several patients treated in this way, as well as with anti-CD20 monoclonal antibodies, have experienced treatment-related adverse events [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Four reported an overall negative outcome at 1 year (42,76,77). The one positive trial used glucagon stimulated C-peptide as an outcome and reported results after only 9 months of follow-up (39).…”
Section: Therapies Used For Interventionmentioning
confidence: 91%